In pursuit of excellence - Orlick, Terry (Human Kinetics, 2008)
Provides various insights and a step-by-step plan for the reader to develop their own personal path to excellence. This book helps the reader to learn to focus for excellence and high-quality living; and, gain a positive outlook, a focused commitment, better ways of dealing with distractions, and strategies for overcoming obstacles.